Paradiplomacy and Democratic Resilience in the Sahel: Subnational Strategies Against Democratic Reversals - Idrees Mahmud Gana; Suleiman Mohammed Evuti (Journal of Paradiplomacy and City Networks, 2025)
Since 2020, the Sahel has witnessed a dramatic resurgence of military coups, with democratic institutions collapsing in Mali, Guinea, Burkina Faso, Chad, and Niger. The Economic Community of West African States (ECOWAS), traditionally positioned as a custodian of constitutional order, has responded with sanctions, suspensions, and threats of intervention. However, these state-centric measures have achieved limited success and often exacerbated humanitarian crises. This article argues that subnational actors, through paradiplomatic practices, have emerged as critical agents of democratic resilience. Drawing on secondary data, policy documents, and scholarly literature, the study integrates a paradiplomacy theory with multi-level governance and “democracy from below” perspectives. It demonstrates how city-to-city networks, cross-border municipal cooperation, and civil society coalitions sustain governance functions and uphold democratic norms in contexts of national authoritarian consolidation. The findings suggest that durable strategies for countering democratic reversals must combine ECOWAS’s top-down enforcement with subnational, bottom-up resilience mechanisms. The article contributes empirically by analyzing Sahelian cases, theoretically by extending the concept of paradiplomacy to fragile states, and normatively by proposing multi-layered responses to the resurgence of authoritarianism.